Arrhythmogenic right ventricular dysplasia: a rare case report from tribal zone of Central India - Khunte, Prakash; Beck, Pradeep; Basal, Bajrang (International Journal of Research in Medical Sciences, 2017)
Arrhythmogenic Right Ventricular Dysplasia (ARVD) is under diagnosed cardiomyopathy which commonly presents in young adults with ventricular tachycardia or sudden death. It is characterized pathologically by progressive fibrofatty replacement of the myocardium, primarily of the right ventricular free wall. Clinically, it presents with life-threatening malignant ventricular arrhythmias which may lead to sudden death, most often in young people and athletes. ARVD/C is difficult to diagnose, although standardized diagnostic criteria have been proposed, based on the presence of major and minor criteria encompassing electrocardiographic, arrhythmic, morphofunctional, histopathologic, and genetic factors.